KNOWLEDGE-PRACTICE DISCONNECT IN MALARIA PREVENTION: A CROSS-SECTIONAL STUDY OF FUTURE HEALTHCARE PROVIDERS IN NIGERIA - Nwadiuto, Ifeoma; Green, Pauline; Briggs, Nduye; Ositadinma, Pius; Onyekwere, Nnanna; Owhonda, Golden; Etiga, Desire; Adoo, Doris (African Journal of Research in Medical and Health Sciences, 2025)
Background: Malaria remains a significant public health challenge in Nigeria. Translating knowledge into preventive practice remains a persistent barrier, even among healthcare trainees. This study assessed the knowledge, attitudes, and practices (KAP) of malaria prevention among clinical medical students at Rivers State University, Nigeria, with a focus on the gap between knowledge and practice. Methods: A descriptive cross-sectional study was conducted among clinical medical students (400–600 level) at Rivers State University using a whole-population sampling approach. Data were collected using a pretested, self-administered questionnaire adapted from WHO malaria prevention indicators. Variables included socio-demographic characteristics, knowledge, attitudes, and practices related to malaria prevention. Data were analyzed using SPSS version 25. Associations between knowledge and practice were assessed using the Chi-square test, with p < 0.05 considered statistically significant. Results: Out of 208 respondents, 48.6% had good knowledge of malaria prevention strategies, and 88.0% demonstrated positive attitudes. However, only 9.6% reported consistent preventive practices. Use of long-lasting insecticide-treated nets (LLINs) every night was reported by 37% of students. Knowledge scores were not significantly associated with good practice (p=0.12), indicating a substantial knowledge-practice gap. Conclusion: Despite moderate knowledge and highly positive attitudes toward malaria prevention among clinical medical students, preventive practices remain suboptimal. Strategies should focus on behavior-change interventions, structured malaria-prevention modules in medical curricula, and the provision of enabling resources to facilitate consistent practice.